The Effect of Paylater Use on Consumer Decisions in Purchasing Travel Packages - Fardhoni Fardhoni; Ayi Muhiban; Andinna Ananda Yusuff; Nining Latianingsih; Dede Yusuf Maulana (Goodwood Publishing, 2026)
Purpose: This study examines the influence of the PayLater feature on consumer decisions when purchasing travel packages. This study addresses the limited empirical research on BNPL usage in the tourism sector and adopts the Technology Acceptance Model (TAM) to explain consumer behavior regarding digital payment adoption. Research Methodology: A quantitative associative approach was employed using a sample of 100 active users of Online Travel Agent (OTA) platforms in Jakarta, Bandung, Purwakarta, and Cirebon. Respondents were selected through purposive sampling based on their experience with PayLater services. Data were analyzed using validity and reliability tests, classical assumption testing, and simple linear regression analysis with the assistance of SPSS software to evaluate the effect of PayLater usage on purchasing decisions. Results: The Paylater feature positively and significantly affected purchasing decisions. The availability of instant credit access and the perceived benefits of fintech services enhance consumer confidence and reduce financial and psychological barriers to spending. The regression results show that PayLater usage explains 46.8% of the variation in purchasing decisions. Conclusions: PayLater facilitates the transformation of purchase intention into actual transactions, especially for high-value travel products, thereby strengthening digital consumer behavior. Limitations: This study focused only on Indonesian OTA users and did not incorporate psychological or social influencing factors. Contributions: The findings provide practical insights for OTA providers, marketers, and policymakers to improve digital payment systems, enhance consumer trust, and develop more effective marketing strategies.